Renewal of an Agreement when a Plant Closes Down (Relations industrielles / Industrial Relations, 1961)
SummaryBy a majority decision, the Board recommends the maintenance of the statu quo subject to the proviso that if the Company renews operations, the Union's right shall be recognized a new.Dispute between Waterloo Plywood Limited and International Woodworkers of America, Local 205, Chairman, Henri T. P. Binet; Employer's member, K. A. Wilson; Employees' member (dissenting), Fernand Daoust, 26th of October, 1960. Ministère du Travail, no 1491-1960.